Design of a Measurement Instrument for the Self-Perception of Architecture Students: Equality, Well-being and Work Expectations - Ochoa Perdomo, Valery Anayansi (LACCEI, 2025)
This paper addresses the need for diagnostic tools with a gender perspective in higher education, focusing on the field of architecture. It proposes the design of a structured questionnaire to explore the self-perception of female university students in three key areas: academic equality, psychological well-being, and career expectations. The instrument is based on consolidated theoretical frameworks and aims to generate quantitative data that can identify gaps, burnout risks, and resilience levels. This article details the instrument's construction, its theoretical foundations, and its potential applications as a diagnostic tool for academic institutions. It is concluded that the implementation of this instrument can catalyze actions for more equitable and inclusive education, laying the groundwork for future larger-scale research to validate its findings in broader populations